Framework humanization enhances GM3(Neu5Gc)-targeting CAR-T cell function by reducing tonic signaling - Tu, Jiaxin; Li, Xinyu; Zhu, Yuge; Li, Shance; Zhang, Guanyu; He, You; Zhang, Chaoting; Lu, Zheming (Frontiers in Immunology, 2025)
GM3(Neu5Gc), a tumor-associated ganglioside absent in normal human tissues due to a CMP-N-acetylneuraminic acid hydroxylase (CMAH) mutation, is an attractive target for solid tumor immunotherapy. To advance the clinical potential of GM3(Neu5Gc)-targeted CAR-T cells, we systematically evaluated antibody humanization by comparing CARs based on the murine 14F7 antibody and its humanized variant 14F7hT. Within each scFv framework, we further assessed three hinge domains (CD8α, CD28, IgG4) to optimize CAR design. While hinge selection influenced in vitro cytotoxicity—favoring CD28—the humanized 14F7hT-based CARs consistently outperformed their murine counterparts in vivo. The optimized 14F7hT-CD28 CAR-T cells demonstrated superior expansion, persistence, tumor infiltration, and antitumor efficacy in xenograft models. To further characterize the basis of this in vivo advantage, we performed a repeated tumor stimulation assay mimicking chronic antigen exposure in solid tumors. In this setting, hGM3/CD28 CAR-T cells exhibited enhanced cytotoxicity, degranulation, and proliferation, supporting improved functional durability. Mechanistically, this was linked to reduced tonic signaling: CAR-Toner predicted a near-optimal signal strength for hGM3/CD28 (score 59) versus excessive signaling in mGM3/CD28 (score 65). This was confirmed experimentally by lower basal cytokine secretion and activation marker expression in cytokine- and antigen-free conditions. Despite preserving complementarity-determining regions, scFv humanization induced subtle structural changes that attenuated tonic signaling and enhanced CAR-T functionality. These findings underscore a critical, previously underappreciated role for antibody framework regions in modulating CAR signaling and therapeutic efficacy. Our study establishes 14F7hT-CD28 as a promising candidate for GM3(Neu5Gc)-positive tumors and highlights framework humanization as a key strategy to improve CAR-T cell performance.